Applying lysozyme, alkaline protease, and sodium hypochlorite to reduce bioclogging during managed aquifer recharge: A laboratory study. (15th April 2023) - Liu, Jinhui; Xia, Lu; Xu, Zilin; Wu, Wenli; Gao, Xiaobing; Lin, Lei
Abstract: Alleviating bacterial-induced clogging is of great importance to improve the efficiency of managed aquifer recharge (MAR). Enzymes (lysozyme and alkaline protease) and sodium hypochlorite (NaClO) are common biological and chemical reagents for inhibiting bacterial growth and activity. To investigate the applicability of these reagents to reduce bioclogging, percolation experiments were performed to simulate a weak alkaline recharge water infiltration through laboratory-scale sand columns, with adding 10 mg/L lysozyme, alkaline protease, and NaClO, respectively. The results showed that, with the addition of lysozyme, alkaline protease, and NaClO, the average clogging rates (the reduced percentages of relative saturated hydraulic conductivity of the sand columns per hour during the percolation experiments) were 0.53%/h, 0.32%/h and 0.06%/h, respectively, which were much lower than that in the control group (0.99%/h). This implied that bioclogging could be alleviated to some extent following the treatments. For further analyzing the mechanisms of the regents on alleviating bioclogging, the bacterial cell amount and extracellular polymeric substances (EPS) concentration were also measured to study the effects of lysozyme, alkaline protease, and NaClO on bacterial growth and EPS secretion. Lysozyme and alkaline protease could disintegrate bacterial EPS by hydrolyzing polysaccharides and proteins, respectively, while they had little effect on the bacterial cell amount. The addition of NaClO significantly decreased the bacterial cell amount ( P < 0.05) and thus greatly alleviated bioclogging. Although the lowest average clogging rate was achieved in the NaClO group, it can generate disinfection by-products that are potentially harmful to the environment and human health. Therefore, the biological-based method, i.e., enzyme treatment, could be a promising option for bioclogging control. Our results provide insights for understanding the mechanisms of lysozyme, alkaline protease, and NaClO to alleviate bioclogging, which is of great importance for addressing the clogging problem during MAR activities and achieving groundwater resources sustainable utilization. Highlights: Lysozyme, alkaline protease, and sodium hypochlorite could reduce bioclogging. Sodium hypochlorite alleviated bioclogging by removing bacteria and dissolving EPS. Lysozyme and alkaline protease hydrolyzed PSs and PNs, respectively. Enzymes are promising options to reduce bioclogging in managed aquifer recharge.